Urban Marketing of Small Cities - Anna Polska; Jan Polski (Barometr Regionalny, 2017)
In the politics of the regional and local development much less attention is devoting itself to small cities compared with large urban agglomerations. However a territorial cohesion of regions is seriously dependent on the amount and the level of development of small cities. Justifying the need of marketing assisting of the development of these economic individuals is the purpose of this article. The practice of the planning and the marketing management is poorly popularized especially in regions of Eastern Poland. In this article authors are stressing the need of assisting attraction of small cities towards basic groups, in it of residents, diverse companies, institutions and social organizations as well as visitors. The small cities are in the regions the specific „pumping stations” of the production, services, capital and information from the larger centers to one’s back. On the example of the poorly urbanized Lubelskie Voivodship it is possible to state that the net of cities is too rare. Low urban planning standards are characteristic of small cities. The urban planning marketing can be the direction of the improvement of the social, economic and spatial situation of such regions as the Lubelskie Voivodship. Amongst this tools a main role will be playing the improvement in the standards of the technical and social infrastructure and comprehensive preparing the new investment grounds for the settlement and the market business activity. The improvement in the corporate culture of local governments in cooperation with all sorts partners on the local and regional level will also be needed.